first what you have to do you have to find the common denominator which is 24
it's 24 because 8 times 3 equals 24 and 12 times 2 equals 24 so they have a like denominator so what you have to do to the bottom you have to do to the top so 8 times 3 is 24 so 3 times 3 is 9 so the new fraction is 9/24. Then 1/12 12×2=24 and 1×2= 2 so the new fraction is 2/24. that would leave you with the problem of 9/24 + 2/24 which is 11/ 24
The perimeter of a triangle is the sum of all side lengths of the triangle. The numerical expression for the perimeter of Stephanie's triangle is: ![\frac 12 \times 25](https://tex.z-dn.net/?f=%5Cfrac%2012%20%5Ctimes%2025)
Let the sides of Juan's triangle be x, y and z. So:
![x = 5 \\ y = 8\\ z = 12](https://tex.z-dn.net/?f=x%20%3D%205%20%5C%5C%20y%20%3D%208%5C%5C%20z%20%3D%2012)
The perimeter (J) of Juan's triangle is calculated by adding all sides.
So:
![J =x +y +z](https://tex.z-dn.net/?f=J%20%3Dx%20%2By%20%2Bz)
This gives:
![J =5 + 8 + 12](https://tex.z-dn.net/?f=J%20%3D5%20%2B%208%20%2B%2012)
![J =25](https://tex.z-dn.net/?f=J%20%3D25)
From the question, we understand that:
The perimeter (S) of Stephanie's triangle is half that of Juan.
This means that:
![S = \frac 12J](https://tex.z-dn.net/?f=S%20%3D%20%5Cfrac%2012J)
Substitute 25 for J
![S = \frac 12 \times 25](https://tex.z-dn.net/?f=S%20%3D%20%5Cfrac%2012%20%5Ctimes%2025)
Hence, the numerical expression for the perimeter of Stephanie's triangle is: ![\frac 12 \times 25](https://tex.z-dn.net/?f=%5Cfrac%2012%20%5Ctimes%2025)
Read more about perimeters at:
brainly.com/question/11957651
Answer:
1. C. Yes, because a sum of cubes can be factored
2a. false
2b. false
2c. true
2d. false (based on what is written in the equation; refer to step-by-step)
Step-by-step explanation:
1. Both 3 and 8 can be cubed, which is why x^3+8 can be factored (x+2)(x^2-2x+4)
2a. a^2-b^2 can be factored by the perfect square rule, so it should be (a-b)^2
2b. both terms are perfect squares, so you can factor, making it (a+b)(a-b)
2c. You can factor using the perfect square rule, making it (a+b)^2
2d. Most of what is in the equation is true, yet the correct solution would be (a-b)(a^2+ab+b^2)
there is no B i see A and -5A unless its for -5A??